Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Assuming $$ A=\left(\begin{matrix}0 & \sqrt{3}\\\sqrt{3}\ &4\end{matrix}\right)$$ how to find B such that $$A^{51}=B$$ My attempts:

if find $P,D$ that $D$ be diagonal matrix $A=P^{-1} DP$ then $$A^{51}=P^{-1} D^{51}P$$ therefore $B=P^{-1} D^{51}P$ but how to find $D$ and $P$?

Thanks for any hints.

share|improve this question
    
Compute the eigenvectors of $A$. –  David Wheeler Jan 27 '13 at 19:32
    
...together with the eigenvalues. The eigenvalues constitutes $D$, and eigenvectors...$P$. –  Tapu Jan 27 '13 at 19:33
    
A has real eigen value but let A have complex eigen value then eigen vector correspond to this eigen vector has two part (imaginary and real ) how find p now ? –  Maisam Hedyelloo Jan 27 '13 at 19:45
add comment

4 Answers

up vote 2 down vote accepted

Here's another way. The generating function of $A^n$ is $$G(t) = \sum_{n=0}^\infty t^n A^n = (I-tA)^{-1} = \dfrac{1}{-1+4t+3t^2} \left( \begin {array}{cc} -1+4\,t&-t\sqrt {3}\\ -t \sqrt {3}&-1\end {array} \right) $$ Now using a partial fraction decomposition $$ \eqalign{\frac{1}{-1+4t+3t^2} &={\frac {\sqrt {7}}{14(t+2/3-\sqrt {7}/3)}}-{\frac {\sqrt {7 }}{14(t+2/3+\sqrt {7}/3)}}\cr &= -\frac{\sqrt{7}}{14} \sum_{n=0}^\infty \frac{t^n}{(-2/3 + \sqrt{7}/3)^{n+1}} +\frac{\sqrt{7}}{14} \sum_{n=0}^\infty \frac{t^n}{(-2/3 - \sqrt{7}/3)^{n+1}} }$$

Thus with $\alpha = -2/3 + \sqrt{7}/3$ and $\beta = -2/3 - \sqrt{7}/3$, the coefficient of $t^{51}$ in $G(t)$ is $$ \dfrac{\sqrt{7}}{14} \left(\frac{-1}{\alpha^{52}} + \frac{1}{\beta^{52}}\right) \pmatrix{-1 & 0\cr 0 & -1\cr} + \dfrac{\sqrt{7}}{14} \left(\frac{-1}{\alpha^{51}} + \frac{1}{\beta^{51}}\right) \pmatrix{4 & -\sqrt{3}\cr -\sqrt{3} & 0\cr}$$

share|improve this answer
add comment

You would find the eigenvalues and eigenvectors for the matrix $A$.

You should get:

$$\lambda_1 = 2 + \sqrt{7}, v_1 = \left(\left(\frac{-2 + \sqrt{7}}{\sqrt{3}}\right), ~1\right)$$

$$\lambda_2 = 2 - \sqrt{7}, v_2 = \left(-\left(\frac{2 + \sqrt{7}}{\sqrt{3}}\right), ~ 1\right)$$

This forms the Jordan Normal Form, with

$$J = P^{-1}DP$$

You have the columns of $D$ as a linear combination of the eigenvalues.

$$D = [ \lambda_1 | \lambda_2]$$

You have the columns of $P$ as a linear combination of the eigenvectors.

$$P = [ v_1 | v_2]$$

And of course, you can easily find $P^{-1}$.

That should help you move forward.

Regards

share|improve this answer
1  
Clear proof, Amzoti. –  B. S. Jan 27 '13 at 20:03
1  
@BabakSorouh: Thank you, I really like your responses to problems! Regards –  Amzoti Jan 27 '13 at 20:03
    
Great work here! +1 –  amWhy May 6 '13 at 0:12
add comment

What you need is called an Eigendecomposition of the matrix $A$. See for instance http://en.wikipedia.org/wiki/Eigendecomposition_%28matrix%29 or almost any textbook on linear algebra.

share|improve this answer
add comment

You may proceed as follows: Consider the characteristic polynomial $p_A$ of $A$: $$ p_A(\lambda)=\det(A-\lambda I)=\lambda(\lambda-4)-3=\lambda^2-4\lambda-3=(\lambda-2-\sqrt{7})(\lambda-2+\sqrt{7}) $$ Next, for $n \ge 3$, we find $a_n, b_n\in \mathbb{R}$ such that $$ \lambda^n=q(\lambda)p_A(\lambda)+a_n\lambda+b_n. $$ We have $$ (2+\sqrt{7})a_n+b_n=(2+\sqrt{7})^n,\ (2-\sqrt{7})a_n+b_n=(2-\sqrt{7})^n, $$ i.e. $$ a_n=\frac{(2+\sqrt{7})^n-(2-\sqrt{7})^n}{2\sqrt{7}},\ b_n=3\frac{(2+\sqrt{7})^{n-1}-(2-\sqrt{7})^{n-1}}{2\sqrt{7}}. $$ Thanks to the Cayley-Hamilton theorem we have $$ A^n=a_nA+b_nI. $$ Now just take $n=51$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.